BIMBINGAN KELOMPOK DENGAN TEKNIK SELFT MANAGEMENT BAGI SISWA YANG MEMILIKI PERILAKU DISIPLIN RENDAH DALAM PENGUMPULAN TUGAS DARING - Nina Rosalina; Ika Mustika; Tita Rosita (IKIP Siliwangi, 2023)
This study examines the implementation and objectives of group guidance services to determine the effectiveness of self-management techniques on student discipline behavior in collecting assignments given by subject teachers during online learning activities. The method used in this research is descriptive qualitative method, and 8 subjects were selected through purposive sampling technique. The results show that during distance learning, group guidance services with self-management techniques can effectively improve student discipline behavior in collecting online assignments from subject teachers. Based on the results of interviews and documents before and after the study, it was found that students experienced significant behavioral changes in the discipline of collecting online assignments from subject teachers during distance learning activities.Keywords: group guidance, self management, discipline